SUSTAINABLE BANK, FIRM REPUTATION, AND FIRM PERFORMANCE: A MEDIATION MODEL - suprapto, adi teguh (Jurnal Metaverse ADPERTISI, 2023)
Amid the global community's impacts of climate change, unbalanced natural cycles spur increased environmental and social problems. The Covid-19 pandemic is important for various parties to evaluate the importance of implementing environmental, social, and governance aspects, including the banking sector. Sustainable Banking has now become a familiar concept in the economies of developing countries. Other factors influence its implementation in Indonesian banking. This study develops and tests a mediation model explaining how a firm’s reputation can link sustainable banking with improving firm performance. SEM-PLS results from secondary data collected from sustainability reports and annual reports on 45 issuer banks in Indonesia indicate that the positive implementation of sustainable banking, in turn, increases the firm’s reputation and performance. This study contributes to research on the implementation of sustainable baking in developing countries.